Efficiency Maine: Investing in Energy Savings and Knowledge - Vrabel, Tim (Maine Policy Review, 2008)
Tim Vrabel provides an overview of Efficiency Maine, which has programs for business and residential users, technical training, and commercial and agricultural energy auditing.
Keywords: Maine; energy efficiency